2021
DOI: 10.1002/bem.22347
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Environmental and Experimental Factors Influencing Human Perception of DC and AC Electric Fields

Abstract: As part of the energy transition in Germany, high-voltage direct current (HVDC) lines producing DC electric fields (EF) are in planning. Since the human perception of DC EF was rarely investigated in the past, we aimed to identify environmental and experimental factors influencing the human perception of direct current (DC) EF, alternating current (AC) EF, and the co-exposure of DC EF and AC EF (hybrid EF) under whole-body exposure. Additionally, first estimates of DC EF and AC EF perception thresholds as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 14 publications
4
12
0
Order By: Relevance
“…In a recent study of our group, Jankowiak et al [13] outlined experimental and environmental factors influencing EF perception. Therefore, a highly sophisticated whole-body exposure laboratory was built based on the study of Nguyen and Maruvada [12], where DC EF with and without ion current, AC EF, and hybrid EF could be generated.…”
Section: Ef Perceptionmentioning
confidence: 99%
See 4 more Smart Citations
“…In a recent study of our group, Jankowiak et al [13] outlined experimental and environmental factors influencing EF perception. Therefore, a highly sophisticated whole-body exposure laboratory was built based on the study of Nguyen and Maruvada [12], where DC EF with and without ion current, AC EF, and hybrid EF could be generated.…”
Section: Ef Perceptionmentioning
confidence: 99%
“…Ion presence had no statistical significance on the participants' sensitivity. Jankowiak et al [13] observed an interaction between relative humidity and field type leading to the conclusion that high relative humidity (70%) facilitates DC EF perception, whereas low relative humidity (30%) supports the perception of AC EF. Despite the small number of participants, this study provided valuable insights into the feasibility of whole-body EF perception testing and served as a basis for parameter settings in this study, for example, by reducing ramp slope and exposure duration to a minimum of 3 and 5 s.…”
Section: Ef Perceptionmentioning
confidence: 99%
See 3 more Smart Citations